The Complete Convergence for Sequence of Arbitrary Random Variables in Hilbert Space and its Application - Khanh Hang, Bui; Chien, Ta Van (VNU Journal of Science: Mathematics - Physics, 2025)
In this work, we establish the complete convergence for sequences of arbitrary random variables taking values in Hilbert space  with general normalizing sequences. As corollaries, we present some convergence results for  -valued martingale difference sequences. Finally, the complete convergence of degenerate von Mises statistics is investigated.